(NgEOMETRI^ESKAQ TEORIQ MERY (B:s (NpER(B. (NS ANGL(B. /s - (NfEDERER(B, (NgERBERTs; (NbAJBORODOW(B, (Ns(B.(Np(B.s; (NwITU[KIN(B, (Na(B.(Ng(B.s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1987)
(NbIBLIOGR(B.: (NS(B. 751-753 (66 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 757-760s
Keywords: (NmERA MNOVESTWAs